Effects of Apoptin-Induced Endoplasmic Reticulum Stress on Lipid Metabolism, Migration, and Invasion of HepG-2 Cells - Zhu, Yilong; Li, Yiquan; Bai, Bing; Shang, Chao; Fang, Jinbo; Cong, Jianan; Li, Wenjie; Li, Shanzhi; Song, Gaojie; Liu, Zirui; Zhao, Jin; Li, Xiao; et al. (Frontiers in Oncology, 2021)
In this study, we investigated the effects of endoplasmic reticulum (ER) stress induced by Apoptin on lipid metabolism, migration and invasion of HepG-2 cells, and preliminarily explored the relationship between endoplasmic reticulum stress, lipid metabolism, migration and invasion. The effects of apoptin on ER function and structure in HepG-2 cells were determined by flow cytometry, fluorescence staining and by western blotting to determine the expression levels of ER stress related proteins The effects of apoptin on HepG-2 cells’ lipid metabolism were determined by western blot analysis of the expression levels of triglyceride, cholesterol and lipid metabolism related enzymes. The effects of apoptin on HepG-2 cells’ migration and invasion were studied using migration and invasion assays and by Western-blot analysis of the expression of proteins involved migration and invasion. The in vivo effects of endoplasmic reticulum stress on lipid metabolism, migration and invasion of HepG-2 cells were also investigated by immunohistochemistry analysis of tumor tissues from HepG2 cells nude mice xenograft models xenografted. Both in vitro and in vivo experiments showed that apoptin can cause a strong and lasting ER stress response, damage ER functional structure, significantly change the expression levels of lipid metabolism related enzymes and reduce the migration and invasion abilities of HepG-2 cells. Apoptin can also affect HepG-2 cells’ lipid metabolism through endoplasmic reticulum stress and the abnormal expression of enzymes closely related to tumor migration and invasion. These results also show that lipid metabolism may be one of the main inducements that reduce HepG-2 cell migration and invasion abilities.